In-situ photoinduced formation of self-assembled Ag NPs using POSS-TX as nano-photoinitiator in PEGMEA/PEGDA polymer matrix and creating self-wrinkled pattern - Batibay, Gonul S.; Gunkara, Omer Tahir; Ocal, Nuket; Arsu, Nergis (ELSEVIER SCIENCE SA, 2018)
Thioxanthone (TX) and its derivatives are playing an important role as photoinitiators for photo-polymerizable formulations. But another significant role of the photoinitiators was recently discovered, namely, the photoreduction of metal salts to metal nanoparticles, in which mainly ketyl radicals were responsible for this process. Functionalization of Polyhedral Oligomeric Silsesquioxanes (POSS) with DC is reported here and used for simultaneous preparation of self-assembled silver nanoparticles (Ag NPs) with POSS cage and polymer matrix. Covalent attachment of POSS-TX to the polymer matrix resulted in self-assembled Ag NPs in a self-wrinkled pattern. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Photopolymerization; Nanocomposites; Self-assembled; Silsesquioxane (POSS); Silver-nanoparticles; FREE-RADICAL POLYMERIZATION; ACETIC-ACID DERIVATIVES; SILVER NANOPARTICLES; GOLD NANOPARTICLES; II PHOTOINITIATOR; THIOXANTHONE; ANTHRACENE; SYSTEMS; SURFACE; LIGHT; Chemistry